Probe of Fatal Skydiver Accident Continues (Air Safety Week, 2009)
There were several AIRMETs in effect for the accident area. AIRMET Sierra indicated possible ceilings of 1,000 feet and visibility below 3 miles. It also indicated mountain obscuration by clouds, precipitation, and mist. AIRMET Zulu, update 3, indicated that the freezing level was between 5,000 and 9,000 feet. It forecast moderate ice between the freezing level and FL (flight level) 240. AIRMET Tango indicated moderate turbulence below 10,000 feet. The FAA Aeronautical Information Manual, paragraph 8-1-2, "Effects of Altitude," describes hypoxia as "a state of oxygen deficiency in the body sufficient to impair functions of the brain and other organs." The textbook also notes that "an individual breathing air at 8,000 feet may take significantly longer to achieve optimum performance at novel tasks than is the case at sea level. For example, this degree of hypoxia has been found to double the reaction times of initial responses to a complex choice-reaction task as compared with responses at sea level. The intensity of this effect increases with altitude and complexity of the task - markedly so above 12,000 feet." (Gradwell, 2006, p. 51). Studies also noted that research subjects exhibited mental performance impairment during task tests that were begun after only 5 minutes (Kelman, G.R.; Crow, T.J. 1969. Impairment of mental performance at a simulated altitude of 8,000 feet. In: Aerospace Medicine 40 (9). pp. 981-982) and 10 minutes (Denison, D.M.; Ledwith, F.; Poulton, E.C. 1966. Complex reaction times at simulated cabin altitudes of 5,000 feet and 8,000 feet. In: Aerospace Medicine. pp. 1010-1013. October 1966) of exposure to a simulated altitude of 8,000 feet. The study indicated that the airplane was changing altitudes and turning before making an abrupt 360-degree turn, and lost over 10,000 feet in 2 minutes. The descent rate approached 8,000 feet per minute (fpm). The last target was at 8,900 feet at 1959:40. One of the three radar sites used appeared to have captured the first sign of the airplane stalling about 1957:33. Therefore, the specialist used data from only one radar site in the performance calculations, and these were limited to the time prior to the stall. During the last 360-degree turn, there were several other indications of the airplane approaching a stall followed by recovery. The airplane appeared to completely depart controlled flight around 1959.